Creative Teaching in Mashhad University of Medical Sciences: Students’ Viewpoints in School of Nursing and Midwifery - Sakineh Mohebiamin; Hossein Jafari Suni; Mahmood Saeedy Rezvani; Amir Amin Yazdi (مجله ایرانی آموزش در علوم پزشکی, 2013)
Introduction: Creative teaching is one of the most basic requirements in the modern higher education systems. The aim of this study is to investigate the status of creative teaching from the viewpoints of students studying in School of Nursing and Midwifery at Mashhad University of Medical Sciences. Method: This descriptive survey study was performed on a stratified sample of 246 students (nursing, anesthesiology, operation room, and midwifery) of School of Nursing and Midwifery of Mashhad University of Medical Science in year 2012. Data gathering tool was a questionnaire made by researcher including 55 items (with 5 points Likert scale) in 10 domains according to Ekvall’s Organizational Climate for Creativity. Data was analyzed using one sample T-test, ANOVA and MANOVA Test. Results: Mean and standard deviation of questionnaire’s total score (3.11±.52) was significantly (t=9.21, p=0.001) more than that of the scale’s cut point (=3), indicating the desirability of creative teaching from students’ perspective. The total mean score for all factors of creative teaching was 3.36±.47 in nursing, 3.12±.58 in anesthesiology, 3.67±.52 in operation room, and 3.31± .52 in midwifery discipline. The difference between mean scores of different disciplines was statistically significant (F=12.36, p= 0.001) Conclusion: This study showed that teachers’ creativity in teaching is desirable from the students' viewpoints in school of nursing and midwifery of Mashhad Medical University. Moreover, midwifery teachers acted more creatively compared to the other disciplines under investigation